To keep or divest a division: Canon's strategy in an oligopolistic market. Issue 2 (4th October 2022) - Redegeld-Geenen, Mara; Kruis, Anne-Marie; Sneller, Lineke
The issue in this teaching case is the future of the Lithography Division of Canon. The case is situated in 2015 when this division represents around 7.5% of the company's assets, 13.8% of its sales, and 10% of its capital expenditures. The division is loss-making. This issue is faced by two persons in the organization: the CEO and the CFO of Canon. The CEO would like to keep the division, while the CFO prefers to divest it. The case is particularly interesting because of the market structure: the division operates in the lithography market, which is a clear example of an oligopoly. The case can be used in Strategy, Technology, or Digital Business courses in MSc or MBA programs. The learning objectives of the case are (1) combining information provided via academic journals with facts from the case and the collective knowledge and creativity of a team of students, (2) analyzing the collected information and building a case with strong arguments, (3) creating a convincing strategic plan including a persuasive presentation, and (4) practicing the skills of presenting. The information provided in this case is based on the annual reports of Advanced Semiconductor Materials Lithography (ASML), Canon, and Nikon, and on other publicly available information on the lithography industry. The case itself is fictional. The authors are not aware of any discussions within Canon about the future of the company's lithography division.